2013
DOI: 10.1371/journal.pone.0083492
|View full text |Cite
|
Sign up to set email alerts
|

Spectral CT Imaging of Laryngeal and Hypopharyngeal Squamous Cell Carcinoma: Evaluation of Image Quality and Status of Lymph Nodes

Abstract: PurposeThe purpose of this study was to evaluate image quality and status of lymph nodes in laryngeal and hypopharyngeal squamous cell carcinoma (SCC) patients using spectral CT imaging.Materials and MethodsThirty-eight patients with laryngeal and hypopharyngeal SCCs were scanned with spectral CT mode in venous phase. The conventional 140-kVp polychromatic images and one hundred and one sets of monochromatic images were generated ranging from 40 keV to 140 keV. The mean optimal keV was calculated on the monoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Computerized tomography and laryngoscopy are the main laryngeal cancer diagnostic and staging modalities. Computerized tomography clearly reveals the anatomic relationship between the tumour and surrounding normal tissues, as well as lymph node metastasis . With NBI laryngoscopy, typical lesions can be acquired according to IPCL morphology, and different laryngeal diseases, including carcinomas, benign tumours, polyps and inflammation, can be identified .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computerized tomography and laryngoscopy are the main laryngeal cancer diagnostic and staging modalities. Computerized tomography clearly reveals the anatomic relationship between the tumour and surrounding normal tissues, as well as lymph node metastasis . With NBI laryngoscopy, typical lesions can be acquired according to IPCL morphology, and different laryngeal diseases, including carcinomas, benign tumours, polyps and inflammation, can be identified .…”
Section: Discussionmentioning
confidence: 99%
“…However, serum marker examination is not the first option because of the long diagnostic period for laryngeal carcinoma. Imaging examinations, including magnetic resonance imaging (MRI) and computerized tomography (CT), provide the best opportunity to determine the tumour range, the anatomical relationship between the tumour and surrounding normal tissues, and the presence or absence of lymph node metastasis . However, CT and MRI cannot detect early‐stage laryngeal carcinoma.…”
mentioning
confidence: 99%
“…Besides, the current clinical examination method has limitations, which are the main reasons of treatment failure (Parmar et al, 1998). Ji et al (2001) and Li et al (2013) found that cN0 cervical lymph nodes in supraglottic carcinoma metastasis were mainly located in areas II, III, IV, which accounted for 96% of cases, and areas I and IV were rarely involved. In 1999, the Brazilian Head and Neck Cancer Group published the results of a randomized study of 132 cases of selective neck dissection vs modified radical neck dissection in the management of cN0 supraglottic and transglottic carcinomas, which showed that the two groups' cervical lymph node metastasis rates were 4.8 and 2.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-energy computed tomography (DECT) with the latest gemstone detector allows for reconstruction of virtual monochromatic images and material decomposition images 8 9 10 11 12 and provides multiple quantitative parameters that have been used for the diagnosis of lymph node metastasis for several types of tumours 12 13 14 15 . However, to our knowledge, the value of DECT for the preoperative diagnosis of cervical nodal metastasis in patients with different malignant carcinomas has not been well evaluated.…”
mentioning
confidence: 99%